Single‐cell profiling of circulating and brain‐resident immune cells in a mouse model for amyloidosis and in aged mice: Inflammation: From basic science to biomarkers. (7th December 2020) - van Olst, Lynn; Verhoeff, Jan; Schetters, Sjoerd T.T.; Hulshof, Lianne A.; van Dijk, Roland; van der Pol, Susanne M.A.; Schouten, Marijn; Vallejo, Juan J. Garcia; van Der Flier, Wiesje; Teunissen, Charlotte E.; Middeldorp, Jinte; de Vries, Helga E.
Abstract: Background: Emerging evidence suggests that peripheral immunity plays an important role in the progression of Alzheimer's disease (AD) (Gate et al., 2020). However, more understanding on how peripheral immune cells respond to AD pathology is needed before utilizing the immune system further for early diagnosis and therapeutic treatment. Here, we aimed to map the immune system in the early stages of amyloidosis. In addition, we aimed to characterize the aged immune system and to study the effect of age‐related circulating immune factors on the immune response. Method: We used 6‐month‐old APPswe/PS1dE9 (APP/PS1) transgenic and wild type (WT) mice to study the immune response to amyloid‐beta pathology and 20 month‐old WT mice for characterization of the aged immune system. In addition, both 6‐month‐old WT and APP/PS1 mice received multiple injections with aged blood plasma derived from 20‐month‐old WT mice. Next, immunohistochemical and high‐dimensional single‐cell analysis using time‐of‐flight mass cytometry (CyTOF), allowing detection of different immune populations and their activation status, was performed to map the circulating and brain‐resident immune cells in the different conditions (Figure 1). Result: Immunohistochemical analysis revealed that T cell infiltration in the 6‐month‐old APP/PS1 brain coincided with early amyloid‐beta plaque formation. Single cell analysis of circulating and brain‐resident immune cells of APP/PS1 mice showed that especially T cells clustered in different cell‐subsets and had increased expression of activation and cell‐adhesion molecules compared to young WT mice. In contrast, circulating and brain‐resident T cells of aged mice contained more regulatory cell subsets and increasingly expressed molecules involved in immune inhibition. Interestingly, initial analysis revealed that injections with aged WT blood plasma partially reduced the aforementioned differences in T cells between young WT and APP/PS1 mice. Conclusion: We found that circulating and brain‐resident T cells were different in their subsets and expression profile in early amyloid‐beta accumulation and in aging. In addition, the activation status of APP/PS1‐derived T cells was reduced after exposure to aged WT blood plasma resulting in a T‐cell signature more similar to young WT mice. Currently, we are further investigating the peripheral immune response to amyloid‐beta pathology by lipid‐ and RNA profiling of the circulating immune cells.